Development of a transformation system for Gracilaria changii (Gracilariales, Rhodophyta), a Malaysian red alga via microparticle bombardment - Sook, Yee Gan; Song, Qin; Othman, Rofina Yasmin; Siew, Moi Phang (Penerbit Universiti Sains Malaysia, 2004)
Of the seaweed phycocolloids, agar has the higher price in the world market and is mostly extracted from red seaweeds. Critchley (1993) reported the world market value of agar as US $200 million. Hurtado-Ponce and Umezaki (1988) reported that the world's commercial agar comes mostly from gracilaroids.